Health status of uruguayan people - Rossi, Ianina (Estudios de Economía, 2016)
In this paper we analyze the links between health status (measured by selfreportedillness occurrence) and individuals’ socioeconomic situation. Usingthe annual households surveys of Uruguay for the period 1991 to 2000, wecompute probit models and find that men, unmarried, young people, occupied,those who do not live alone and those with more than 5 years of education, havea smaller probability of reporting a bad health status. We also find that theprobability of reporting a bad health status has a descendent trend in the period,falling from 0,33 in 1991 to 0,25 in 2000.